2017
DOI: 10.1177/0885066617724340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clevidipine and Nicardipine for Acute Blood Pressure Reduction in Patients With Stroke

Abstract: There was no difference in the mean time from initiation of the infusion to the SBP goal between agents or in the secondary outcomes. Due to the lack of differences observed, each agent should be considered based on the patient care needs of the institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Given the considerable difference in the management of ischemic and hemorrhagic stroke, separate evaluation appeared warranted. This study found no significant difference in time to goal SBP between nicardipine and clevidipine, which supports previous findings in the combined patients with ischemic and hemorrhagic stroke [11,14,15]. Additionally, percentage of time at goal was similar between groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Given the considerable difference in the management of ischemic and hemorrhagic stroke, separate evaluation appeared warranted. This study found no significant difference in time to goal SBP between nicardipine and clevidipine, which supports previous findings in the combined patients with ischemic and hemorrhagic stroke [11,14,15]. Additionally, percentage of time at goal was similar between groups.…”
Section: Discussionsupporting
confidence: 90%
“…AHA/ASA guidelines have not specified a preferred titratable antihypertensive agent. There have been three retrospective direct comparisons of nicardipine with clevidipine in patients with ischemic and hemorrhagic stroke [11,14,15]. There was no significant difference in time to goal SBP between nicardipine and clevidipine in all three studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A retrospective cohort study involving 210 patients in the emergency department with ischemic or hemorrhagic strokes established that clevidipine (50 [SD, 83] minutes and nicardipine (74 [SD, 103] minutes) both achieved the systolic BP goal (P ÂĽ .101). 12 Therefore, the recommendation is that NPs can use nicardipine or sodium nitroprusside to reduce systolic, diastolic, and mean arterial pressures (MAPs) in an HC.…”
Section: The Mnemonicmentioning
confidence: 99%
“…53 For patients who are critically ill or are to receive tPA or other interventions, clevidipine and nicardipine are the agents of choice for rapidly lowering blood pressure. 32,54 Rapid fluctuations in blood pressure within the first 180 minutes of hospital stay were associated with increased mortality rate within 90 days for acute ischemic stroke patients. As compared to patients with smaller variations in blood pressure, patients who died within 90 days were found to have larger changes in their diastolic blood pressures within the first 180 minutes.…”
Section: Blood Pressure Considerationsmentioning
confidence: 99%